E-Module Cognitive Behavior Modification with Restructuring Techniques to Reduce Cyberbullying Behavior - Fradinata, Suci Amaliya; Karneli, Yeni (Bisma The Journal of Counseling, 2024)
Cyberbullying is a form of bullying that is very vulnerable to occur in adolescence, which is now easier and more often done using electronic or digital devices. Individuals or adolescents who experience cyberbullying can experience depression, anxiety, loneliness, suicidal behavior and symptomatic symptoms. This study aims to analyze the conditions of cyberbullying behavior and produce a product in the form of an e-module for cognitive behavioral modification with a change technique to reduce cyberbullying behavior that is feasible and can be used by BK teachers/Counselors. This study is a type of development research (Research and Development) with the ADDIE model. This study involved 3 experts related to the feasibility test of the content and appearance of the e-module and 2 BK teachers/Counselors to test the usability of the e-module. The research data were analyzed using descriptive statistics and nonparametric statistics. The results of the study showed that the condition of cyberbullying behavior in students was in the high category. The e-module for cognitive behavioral modification with a structuring technique to reduce cyberbullying behavior in students was considered feasible for use by BK teachers/Counselors in reducing cyberbullying behavior and the level of usability of the e-module was considered good.